Variação genética e seleção para caracteres de crescimento em progênies de Eucalyptus camaldulensis Dehnh - Azevedo, Luana Pâmella de Almeida (2013)
The present work this study aimed to estimate parameters, phenotypic and genetic correlations between growth traits, genetic gain and effective population size for growth traits and form in progeny trial of Eucalyptus camaldulensis. The progeny test was installed in a randomized block design with 132 progeny, five replications and three plants in single rows, spaced 3 mx 2 m in Santo Antonio do Leverger, MT. At three years of age, the progenies were evaluated for the following traits: a) total height (ALTT), commercial height (ALTC), diameter at base height (DBH), stem form (FF) and survival (SOB). Estimates of individual heritabilities were of low magnitude for the characters ALTT (0.10), DAP (0.16) and UNDER (0.07). However, the characters ALTC (0.18) and FF (0.25), gave values of medium to high magnitude. For survival, the heritabilities showed up practically nil due to low genetic variability among progenies due to the high survival rate of plants (91.26%). The coefficients of individual genetic variation (CVGI%), ranged from 8.08% to 15.91% for the SOB ALTC. The experimental coefficients of variation (CVe%) found, showed values ranging from 11.68% (FF) to 29.53% (ALTC), considered low and medium for their characters. The accuracies were significant for all the characters, especially for FF (63%) and ALTC (51%), indicating the reliability of the results obtained in genetic evaluation. The phenotypic and genetic correlations were predicted high magnitude for DAB and height. The matrices 15, 126, 37, 43, 100 and 34, showed greater genetic gain across the population compared the top 20 of each character, confirming its superiority to all traits. Estimates of effective population size indicate that the progeny test presents an effective size sufficient for the maintenance of genetic variability in the sequence of genetic improvement program. The selection with BLUP was superior when compared to selection among and within.